Experimental and theoretical investigations of different diketopyrrolopyrrole-based polymers - Murugan, Pachaiyappan; Raghavendra, Venkatraman.; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Mandal, Asit Baran; Subramanian, Venkatesan; Samanta, Debasis (ACS Omega, 2018)
Diketopyrrolopyrrole (DPP)-based polymers are often considered las the most promising donor moiety in traditional bulk heterojunction solar cell devices. In this paper, we report the synthesis, characterization of various DPP-based copolymers with different molecular weights, l and polydisper sity where other aromatic repeating units (phenyl or thiophene based) are connected by alternate double bonds or triple bonds. Some of the copolymers were used for device fabrication and the crucial parameters such as fill factor (FF) and open circuit voltage (V-oc) were calculated. The density functional theory was used to optimize the geometries and deduce highest occupied molecular orbital lowest unoccupied molecular orbital gaps of all the polymers and'theoretically predict their optical and electronic properties. Optical properties of all the polymers, electrochemical properties and band gaps were also obtained experimentally and compared with the theoretically predicted values.